2018
DOI: 10.1177/1558944718820962
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Variations in Volar Cortical Angle of the Distal Radius

Abstract: Background: The ideal volar locking plate for the treatment of distal radius fracture should anatomically fit the volar surface of the distal radius. The purpose of this study was to measure the volar cortical angle (VCA) of uninjured adult distal radii to determine how well the VCA matches that of modern volar locking plates and whether variations in the VCA are related to demographic factors. Methods: A retrospective radiographic analysis of 273 uninjured adult distal radii was performed. Patients were strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These studies observed that the angles of volar inclination of the radius were greater in men. ( 7 , 19 - 21 Gandhi et al ( 3 described that the PCA decreases with age, and men have a higher mean PCA, suggesting that current locking plates fit better in older women. Kwon et al ( 11 studied differences between Caucasian and Korean individuals, noting that Koreans presented a greater width of the distal region of the radius compared to Caucasians, as well as Korean men when compared with Korean women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies observed that the angles of volar inclination of the radius were greater in men. ( 7 , 19 - 21 Gandhi et al ( 3 described that the PCA decreases with age, and men have a higher mean PCA, suggesting that current locking plates fit better in older women. Kwon et al ( 11 studied differences between Caucasian and Korean individuals, noting that Koreans presented a greater width of the distal region of the radius compared to Caucasians, as well as Korean men when compared with Korean women.…”
Section: Discussionmentioning
confidence: 99%
“…Fractures in the distal end of the radius are frequent in an orthopedic surgeon's routine, being responsible for 18% of all fractures. [1][2][3][4] They present a bimodal distribution, affecting mainly children between the ages 10 and 14 and women over 50, the latter related to bone fragility. 5 Currently, several therapeutic options are available: plaster casts, external fixators, percutaneous pin fixation, and modern locking volar plates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the volar cortical angle was reported as the angle formed by a straight line drawn along the volar surface of the distal radius and a line drawn parallel to the volar cortex. 18 The normal volar cortical angle of a man was reported from 30.4 to 34.1 . 18 In the model, the volar cortical angle was 31 .…”
Section: Angulated Distal Radius Modelingmentioning
confidence: 99%
“…18 The normal volar cortical angle of a man was reported from 30.4 to 34.1 . 18 In the model, the volar cortical angle was 31 . Five additional models were developed, based on the intact wrist model, to simulate the dorsally-angulated distal radius.…”
Section: Angulated Distal Radius Modelingmentioning
confidence: 99%